Photosynthetic diffusional constraints affect yield in drought stressed rice cultivars during flowering - Lauteri, Marco; Haworth, Matthew; Serraj, Rachid; Monteverdi, Maria Cristina; Centritto, Mauro (Public Library of Science, 2014)
Global production of rice (Oryza sativa) grain is limited by water availability and the low ‘leaf-level’ photosynthetic capacity of many cultivars. Oryza sativa is extremely susceptible to water-deficits; therefore, predicted increases in the frequency and duration of drought events, combined with future rises in global temperatures and food demand, necessitate the development of more productive and drought tolerant cultivars. We investigated the underlying physiological, isotopic and morphological responses to water-deficit in seven common varieties of O. sativa, subjected to prolonged drought of varying intensities, for phenotyping purposes in open field conditions. Significant variation was observed in leaf-level photosynthesis rates (A) under both water treatments. Yield and A were influenced by the conductance of the mesophyll layer to CO2 (gm) and not by stomatal conductance (gs). Mesophyll conductance declined during drought to differing extents among the cultivars; those varieties that maintained gm during water-deficit sustained A and yield to a greater extent. However, the variety with the highest gm and yield under well-watered conditions (IR55419-04) was distinct from the most effective cultivar under drought (Vandana). Mesophyll conductance most effectively characterises the photosynthetic capacity and yield of O. sativa cultivars under both well-watered and water-deficit conditions; however, the desired attributes of high gm during optimal growth conditions and the capacity for gm to remain constant during water-deficit may be mutually exclusive. Nonetheless, future genetic and physiological studies aimed at enhancing O. sativa yield and drought stress tolerance should investigate the biochemistry and morphology of the interface between the sub-stomatal pore and mesophyll layer.